Effects of ocean states coupling on the simulated Super Typhoon Megi (2010) in the South China Sea - Zheng, Minglin; Zhang, Ze; Zhang, Weimin; Fan, Maoting; Wang, Huizan (Frontiers in Marine Science, 2023)
Responses of the South China Sea (SCS) to a typhoon are complex due to the susceptible upper layer and active multiscale motions and thus need to be urgently resolved and validated in numerical simulations. A coupled atmosphere–ocean–wave model and various in-situ observations were applied to understand the strong interactions between Super Typhoon Megi (2010) and the SCS, especially the wave effects on typhoon simulation. Five sensitive experiments using different combinations of models were firstly conducted and compared to validate the effectiveness of the ocean coupling. Compared with WRF-only and ROMS-only outputs, the coupled experiments evidently improved the accuracy of typhoon intensity, the typhoon-induced cold wake, and significant wave height, along with the thermodynamical responses in the upper 400 m layer, including the near-inertial currents, the variation in ocean heat content, and mixed layer depth. However, the differences between WRF-ROMS and COAWST were slight, though the significant wave height was more than 9 m high in COAWST. Further analysis showed that the modification of heat flux, which could cancel out the effect due to the wave-induced surface roughness, is consistent with that of momentum flux in the wave-coupled experiment. This resulted in similar overall results. To further figure out the wave effects on typhoon and eliminate the contingency brought by the surface physical parameterization scheme, six experiments using three surface physical parameterization schemes were designed with and without wave coupling, separately. The sensible heat flux showed significant differences between three schemes, followed by the latent heat flux and the correspondingly changing momentum loss. Results support the above-mentioned conclusion that the typhoon intensity was determined by the net surface flux. Our findings highlight the necessity in using a high-resolution coupled atmosphere–ocean–wave model and proper surface physical parameterization, especially when coupling waves to make accurate regional numerical environment predictions.